Reliability of the Exchange Rate as a Monetary Target in an Unoptimal Currency Area - Macedonian Case - Gligor Bišev (National Bank of the Republic of Macedonia, 1997)
The main topic of the research work is, whether the exchange rate targeting is an efficient strategy for maintaining price stability without decelerating the economic growth below the potential one in a situation when national currency area is not an optimum currency area with the anchor currency country in the Mundell-McKinnon style. The research work is devided into six chapters. In the first introductory chapter the set up of the Macedonian monetary order is presented, together with the outline what is following in next five chapters. The main topic of investigation in the second chapter is, if there is an alternative efficient strategy, except exchange rate targeting, for maintaining price stability in a small and open economy that is highly integrated into the international trade and financial flows. The research topic in third chapter is what are preconditions for a national currency area to be an optimum currency area. In the fourth chapter the benefits and costs of exchange rate targeting strategy in Macedonia are presented regarding the monetary policy (money supply growth and interest rates), domestic prices, international competitiveness and employment and output. In the fifth chapter, the regime of the exchange rate that is appropriate for intermediate monetary target and viable on long-run is analyzed from the point of view of eight factors: openness and integration into the world economy, the scope of concentration of trade towards particular regions or countries, the level of currency substitution in the domestic economy, the depth of financial and foreign exchange market, the level of wage elasticity and labour mobility, the degree of capital mobility, the stability/instability of money demand, the scope of product and export diversification and the level of economic development and expected future potential growth. The concluding remarks are presented in the sixth chapter...
Keywords: 330; Geldpolitisches Ziel; Preisstabilität; Wechselkurspolitik; Kleine offene Volkswirtschaft; Mazedonien